Impact of wind on urban trees for selected areas in Kuala Lumpur - Zakaria, Afiq (2018)
Wind is one of the nature’s unique phenomena, which when occurred in a strong form, may cause tremendous effect and major problems causing impact to human and trees, especially in an urban area such as Kuala Lumpur. The main objective of this study was to investigate the winds’ seasonal characteristics and its impact on trees. Daily wind data was obtained from the Malaysian Meteorology Services (MMS) Petaling Jaya station and categorized using descriptive statistics and frequency analysis. Damage tree data from three different areas was obtained from the Landscape and Recreation Development Department, Dewan Bandaraya Kuala Lumpur (DBKL). Result from this study showed that mean maximum wind gust or mean wind velocity ranged between 20.7 m/s and 20.9 m/s throughout from 2012 to 2016 and usually occurred in the month of November and December. The highest mean wind speed from 2012 to 2016 was in month of December with speed reaching 19.26 m/s. September and November were the second highest with speed reaching at 17.36 m/s. Branch breakage was the main type of tree damage followed by stem breakage and uprooting. Tree species most commonly damaged was Rhu (Casuarina nobile) with total 531 incidence (33.27%) within the three district followed by also Rhu tree but different species (Casuarina equisetifolia) with 180 incidence (11.28%) and Tan wattle (Acacia auriculiformis) with 81 incidencee (5.08%).This study concluded that there was no significant relationship between the wind speed and the frequency of urban tree damage in the selected areas in Kuala Lumpur after being tested with Pearson’s Correlation analysis.